2007
DOI: 10.1128/aem.02080-06
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of the Microbial Community Removing Phosphate from Wastewater under Continuously Aerobic Conditions in a Sequencing Batch Reactor

Abstract: All activated sludge systems for removing phosphate microbiologically are configured so the biomass is cycled continuously through alternating anaerobic and aerobic zones. This paper describes a novel aerobic process capable of decreasing the amount of phosphate from 10 to 12 mg P liter ؊1 to less than 0.1 mg P liter ؊1(when expressed as phosphorus) over an extended period from two wastewaters with low chemical oxygen demand. One wastewater was synthetic, and the other was a clarified effluent from a conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
86
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 52 publications
(88 reference statements)
9
86
1
1
Order By: Relevance
“…Their RNA has been difficult to recover in 16S rRNA gene clone libraries (1,12). Semiquantitative fluorescence in situ hybridization analyses of these populations (6) gave data that corresponded well with data obtained by quantitative PCR, suggesting that our method does not introduce significant extraction bias.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Their RNA has been difficult to recover in 16S rRNA gene clone libraries (1,12). Semiquantitative fluorescence in situ hybridization analyses of these populations (6) gave data that corresponded well with data obtained by quantitative PCR, suggesting that our method does not introduce significant extraction bias.…”
mentioning
confidence: 56%
“…Increased safety and a reduced number of pipetting steps make the method suitable for high-throughput analysis. Consequently, it should prove valuable in molecular microbial ecology where current extraction protocols can fail to recover sequences from recalcitrant populations in clone libraries (1,9,12,16).…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that members of the genera Dechloromonas and "Ca. Competibacter" have nitrate reduction abilities and can accumulate internal polyhydroxyalkanoate (PHA) throughout the SBR cycle (46,(54)(55)(56)(57)(58)(59). These results suggested that the nitrite increase observed during the early anoxic phase (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Since the abundances of PAOs are of great interest for EBPR processes, we propose the use of our technique for quick and reliable authentication of PAOs in WWTPs. Traditional models imply that polyphosphate accumulation occurs during aerobic growth or if the cells are exposed to stress situations such as the decrease of external pH or carbon substrate concentration (2). However, recent studies showed that some species still keep polyphosphate granules even under anaerobic conditions (36).…”
Section: Discussionmentioning
confidence: 99%